"Dog" is "God" Spelled Backward: "Poppy Jingles, " the Staff Well-being Spaniel. (1st March 2021) - Carlyle, Donna; Watson, Katie
Abstract : This brief report describes the unique and innovative work of a hospital chaplaincy "Good Samaritan" staff welfare dog named "Poppy Jingles." As the importance of stress prevention and burnout among National Health Service staff (UK) has been highlighted in current policy, the initiative of animal-assisted therapy is both timely and significant. The relevance of inter-species well-being is detailed in this article, describing what can be considered as Poppy's "nonhuman charisma." This includes eliciting specific aspects of well-being which can be thought to correspond to eudaimonic states of human flourishing.